Protamine and BSA–dextran complex emulsion improves oral bioavailability and anti-tumor efficacy of paclitaxel - Guangrui Xu (Drug Delivery, 2020)
Food protein and polysaccharide complex emulsions are safe carriers of hydrophobic drugs and nutrients. To improve oral bioavailability and therapeutic/healthy efficacy of hydrophobic drugs and nutrients, herein, protamine (PRO), a cationic cell-penetrating peptide, was introduced into protein and polysaccharide complex emulsion. The electrostatic complex of PRO and BSA–dextran conjugate (BD) produced by Maillard reaction was used as emulsifier to produce oil-in-water emulsion (@BD/PRO). The BSA molecules were crosslinked at the oil–water interface by a heat treatment and the PRO chains were simultaneously anchored in the interface. BD emulsion (@BD) without PRO was produced for comparation. Paclitaxel (PTX), a hydrophobic antineoplastic drug, was encapsulated in the emulsions with 99% loading efficiency and 6.4% loading capacity. The emulsions had long-term stability. The bioavailability and H22 tumor inhibition efficacy of PTX@BD/PRO were 40% and 70% higher than those of PTX@BD, respectively, after oral administration in the mice. More importantly, orally administrated PTX@BD/PRO had the same anti-tumor efficacy as intravenously injected commercial PTX injection. No abnormality was observed in the main organs of the mice after consecutive oral administration of PTX@BD/PRO. This study indicates that @BD/PRO is an excellent carrier of hydrophobic drugs/nutrients and is suitable for long-term oral administration.